2002
DOI: 10.1007/s00125-002-0927-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced fetoplacental angiogenesis in pre-gestational diabetes mellitus: the extra growth is exclusively longitudinal and not accompanied by microvascular remodelling

Abstract: Aims/hypothesis. Morphometric studies on pregnancies complicated by gestational diabetes mellitus have found no evidence of increased fetoplacental angiogenesis. Here, placentas from control subjects and patients with pre-gestational Type I (insulin-dependent) diabetes mellitus were used to test for differences in measures of angiogenesis and vascular remodelling. Methods. Term placentas were collected from non-diabetic subjects and well-controlled diabetic patients grouped according to duration and severity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(18 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…Several articles included in this systematic review also investigated measures of angiogenesis (31, 35, 41). Two studies adopted the term “redundant capillary connections”, connections that can be removed without disconnecting from the villous capillary bed.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Several articles included in this systematic review also investigated measures of angiogenesis (31, 35, 41). Two studies adopted the term “redundant capillary connections”, connections that can be removed without disconnecting from the villous capillary bed.…”
Section: Resultsmentioning
confidence: 99%
“…Jirkovska et al reported increased measures of angiogenesis, determined by an increase in the mean number of redundant connections per terminal villi, in women with GDM (35, 41) and in women with T1DM (35) compared to controls. While another study reported increased measures of fetoplacental angiogenesis, Mayhew et al (31) determined this increase by comparing capillary volume, surface area and length. Mayhew et al (31) characterized these changes in angiogenesis as exclusively longitudinal and not accompanied by any increase in vascular remodeling or changes in capillary caliber.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations